InlL from Listeria monocytogenes Is Involved in Biofilm Formation and Adhesion to Mucin - Popowska, Magdalena; Krawczyk-Balska, Agata; Ostrowski, Rafał; Desvaux, Mickaël (Frontiers in Microbiology, 2017)
The bacterial etiological agent of listeriosis, Listeria monocytogenes, is an opportunistic intracellular foodborne pathogen. The infection cycle of L. monocytogenes is well characterised and involves several key virulence factors, including internalins A and B. While 35 genes encoding internalins have been identified in L. monocytogenes, less than half of them have been characterised as yet. Focusing on lmo2026, it was shown this gene encodes a class I internalin, InlL, exhibiting domains potentially involved in adhesion. Following a functional genetic approach, InlL was demonstrated to be involved in initial bacterial adhesion as well as sessile development in L. monocytogenes. In addition, InlL enables binding to mucin of type 2, i.e. the main secreted mucin making up the mucus layer, rather than to surface-located mucin of type 1. InlL thus appears as a new molecular determinant contributing to the colonisation ability of L. monocytogenes.